Internalisasi Nilai-Nilai Kepemimpinan Profetik dalam Mata Pelajaran Tarikh pada Siswa Melalui Pembelajaran Cooperative Learning di SD Muhammadiyah Ambarketawang 2 Gamping Sleman - Ibnu Syakur Alsya’bani; Syamsudin Syamsudin (SALIHA: Jurnal Pendidikan & Agama Islam, 2024)
The subject of Tarikh encompasses the study of Islamic history, including narratives of the Prophets and Messengers, the struggles of Prophet Muhammad's da'wah, as well as the presentation of leadership values such as honesty, responsibility, communication skills, and proactiveness. Unfortunately, students often allocate insufficient attention to this subject. Therefore, it is crucial to integrate Tarikh curriculum with more creative teaching methods to enable students to gain a deeper understanding and practical application of these leadership values. This research aims primarily to identify leadership values with prophetic characteristics within the Tarikh subject and how these values are instilled in students through the application of cooperative learning models. The research employs a qualitative approach and is conducted at SD Muhammadiyah Ambarketawang 2. Observation, documentation, and interviews are used to gather data from three sources: the school principal, Islamic studies teacher, and parents. The research findings reveal that prophetic leadership values within the Tarikh subject can be identified from two main sources: the curriculum and the teacher's lesson plans, which encompass the social dimension KI 2. These values are also implicit in the content of the Tarikh curriculum, both explicitly and implicitly stated in textbooks. The identified prophetic leadership values include honesty (shidiq), responsibility (amanah), communication (tabligh), and proactiveness (fathanah). Furthermore, the research demonstrates that teachers have effectively transferred these prophetic leadership values through the implementation of the jigsaw cooperative learning model, proving its efficacy when applied to Tarikh materials.